Differences in the quality of primary medical care for CVD and diabetes across the NHS: evidence from the quality and outcomes framework - Sutton Matt; Guthrie Bruce; McLean Gary (BMC, 2007)
Abstract Background Health policy in the UK has rapidly diverged since devolution in 1999. However, there is relatively little comparative data available to examine the impact of this natural experiment in the four UK countries. The Quality and Outcomes Framework of the 2004 General Medical Services Contract provides a new and potentially rich source of comparable clinical quality data through which we compare quality of primary medical care for coronary heart disease (CHD), stroke, hypertension and diabetes across the four UK countries. Methods A cross-sectional analysis was undertaken involving 10,064 general practices in England, Scotland, Wales and Northern Ireland. The main outcome measures were prevalence rates for CHD, stroke, hypertension and diabetes. Achievement on 14 simple process, 3 complex process, 9 intermediate outcome and 5 treatment indicators for the four clinical areas. Results Prevalence varies by up to 28% between the four UK countries, which is not reflected in resource distribution between countries, and penalises practices in the high prevalence countries (Wales and Scotland). Differences in simple process measures across countries are small. Larger differences are found for complex process, intermediate outcome and treatment measures, most notably for Wales, which has consistently lower quality of care. Scotland has generally higher quality than England and Northern Ireland is most consistently the highest quality. Conclusion Previously identified weaknesses in Wales related to waiting times appear to reflect a more general quality problem within NHS Wales. Identifying explanations for the observed differences is limited by the lack of comparable data on practice resources and organisation. Maximising the value of cross-jurisdictional comparisons of the ongoing natural experiment of health policy divergence within the UK requires more detailed examination of resource and organisational differences.